The Influence of Work Flexibility, Work-life Balance, and Job Satisfaction on Employee Performance in the Remote Working Era - Rifki, Maulana Radiyan; Fauzan, Rizky; Hendri, M Irfani; Fahruna, Yulyanti; Jaya, Arman (Yayasan Sinergi Kawula Muda, 2025)
This study analyzes the work-life balance (WLB) of students who work as celebgams in Pontianak and Palangka Raya. Utilizing a qualitative method through in-depth interviews with seven informants, this research explores how celebgram students manage the balance between academic demands and their careers on social media and identify the challenges they face. The findings indicate significant differences in experiences between celebgam students in the two cities, particularly concerning commercial pressures and time flexibility. The main challenges identified include time management, social pressure, and follower expectations. This research provides important insights into the complexities students face in the digital age and its implications for educational policies and student well-being.